Qualitative analysis of transverse vibrations of the suspended part of washing machines, taking into account their coupling without damping - Alekhin A. S., Alekhin S. N., Shomirzaev S. S. (A breakthrough in science: development strategies, 2017)
In this paper we consider the issue of the need for improved mathematical models of the dynamics of washing machines based on the coherence of the oscillations of the suspension during the spin cycle. Given the equation of oscillations of a suspended part of the washing machines along the horizontal transverse axis, obtained with and without allowance for coupling of the oscillations, their decisions and the results of the qualitative comparison of the dependences of the amplitudes of the oscill
Keywords: математическая модель; колебания; связанные колебания; подвесная часть; уравнения колебаний; стиральная машина